UMP and UMR Policies as Instruments for Poverty Alleviationin Indonesia : An Empirical Review - Bunga Dwi Fani Ritonga; Isnaini Harahap (Proceeding of The International Conference on Business and Economics, 2024)
This study examines the ef ectiveness of the Provincial Minimum Wage (UMP) and Regency/City Minimum Wage (UMR) policies in alleviating poverty in Indonesia, using an in-depth literature study approach. Indonesia, as the fourth most populous country in the world and the largest economy in Southeast Asia, faces major challenges in reducing income inequality and poverty, especially after the economic impact of the COVID-19 pandemic. The UMP and UMR policies are designed to provide a decent standard of living for workers, but their impacts vary widely across provinces and economic sectors. This study finds that while the minimum wage policy can provide benefits for formal sector workers, its ef ectiveness in reducing poverty in the informal sector is limited, given that around 60% of Indonesia's workforce works in the informal sector that is not covered by this policy. In addition, this policy also has the potential to cause economic dislocation in areas with significant income inequality. Economic sectors that rely on cheap labor, such as manufacturing and agriculture, are vulnerable to the negative impacts of this policy. This study suggests adjusting the minimum wage policy to be more flexible and based on local economic conditions to maximize the impact of poverty alleviation.